Disiplin Positif dalam Perspektif Guru: Analisis Empiris dan Model Konseptual Positive Discipline Framework for Educational Administration (PDFEA) di Kabupaten Maluku Tengah - Kalvin Karuna; Henderika Serpara; Jolanda Tomasouw; Julians Marantika (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the persistent gap between teachers' understanding of positive discipline and its implementation practices in schools, particularly regarding the use of punishment as a form of student behavior control. This study aims to analyze teachers' perceptions and practices of positive discipline and develop a conceptual model of its implementation in the context of island educational administration. The study used a mixed methods approach with a sequential exploratory design involving 42 teachers from various levels of education in Central Maluku Regency. Data were collected through questionnaires and in-depth interviews. Quantitative data analysis was conducted using descriptive statistics to determine trends in teachers' perceptions and practices, while qualitative data were analyzed through thematic analysis. The results showed that all teachers had a positive view of non-violent discipline, but approximately 71% of respondents still used punishment as a solution to student behavior. This finding indicates that the conceptual understanding of positive discipline has not been fully internalized in pedagogical practice. This study resulted in the Positive Discipline Framework for Educational Administration (PDFEA) as a conceptual model that emphasizes the importance of teachers' reflective capacity, empathetic communication, and institutional support in building a restorative and humanistic school culture.